2017
DOI: 10.1002/mgg3.282
|View full text |Cite
|
Sign up to set email alerts
|

A mutation creating an upstream initiation codon in theSOX95′UTRcauses acampomelic campomelic dysplasia

Abstract: BackgroundCampomelic dysplasia (CD) is a semilethal developmental disorder caused by mutations in and around SOX9. CD is characterized by multiple skeletal malformations including bending (campomelia) of long bones. Surviving patients frequently have the acampomelic form of CD (ACD).MethodsThis is a single case report on a patient with clinical and radiological features of ACD who has no mutation in the SOX9 protein‐coding sequence nor a translocation with breakpoint in the SOX9 regulatory domain. We include f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Even if the flanking sequence of the new ATG does not completely match to the consensus predicted Kozak sequence ((G/A)NNAUGG), it seems similar to the one flanking the natural PROS1 ATG, suggesting that the new ATG could be identified by the translational machinery and thus used in the cells (Kozak, 1997, 1990). Several works have previously demonstrated that uAUG and uORF are cis-regulatory elements in 5‘UTR that are able to control protein expression by altering the translation efficiency and could subsequently be associated with risk of diseases (Dvir et al ., 2013; Lin et al ., 2019; Orr et al ., 2019; von Bohlen et al ., 2017). Many previously ignored uORFs are now known to act as major post-transcriptional regulatory elements or to be translated to produce bioactive peptides or proteins (Jones et al , 2017; Orr et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Even if the flanking sequence of the new ATG does not completely match to the consensus predicted Kozak sequence ((G/A)NNAUGG), it seems similar to the one flanking the natural PROS1 ATG, suggesting that the new ATG could be identified by the translational machinery and thus used in the cells (Kozak, 1997, 1990). Several works have previously demonstrated that uAUG and uORF are cis-regulatory elements in 5‘UTR that are able to control protein expression by altering the translation efficiency and could subsequently be associated with risk of diseases (Dvir et al ., 2013; Lin et al ., 2019; Orr et al ., 2019; von Bohlen et al ., 2017). Many previously ignored uORFs are now known to act as major post-transcriptional regulatory elements or to be translated to produce bioactive peptides or proteins (Jones et al , 2017; Orr et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Because the constitutive TIS of ENG does not show a robust Kozak consensus sequence and protein translation usually initiates at the first ATG codon, this suggests that the new TIS at −141 is competing advantageously with the constitutive TIS at +1. 5'UTR mutations that alter the initiation codon have been reported as pathogenic mutations for other genetic disorders [26][27][28]. In HHT1, three mutations (c.-9G>A, c.1-10C>T and c.-127C>T), likely involving the generation of a new initiation codon upstream of the constitutive TIS, have been published [19,20,29], whereas no similar mutations have been described in the 5' UTR of ACVRL1, the gene mutated in HHT2.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the 5′UTR as cause of disease has been described for different diseases, including autosomal recessive metabolic disorders (Barbosa, Peixeiro, & Romão, ; Fu et al, ; Semler et al, ; von Bohlen et al, ; Willemsen et al, ) and thus should be considered in patients with autosomal recessive disease in whom only one heterozygous mutation has been found. Indeed, such disease‐causing mutations may be more frequent than previously assumed due to the fact that most clinical DNA testing specifically focuses on the coding regions of genes.…”
Section: Discussionmentioning
confidence: 99%